1994
DOI: 10.1002/path.1711730106
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical investigation of epidermal growth factor receptor expression in ameloblastomas

Abstract: Immunohistochemical analysis was performed to determine the localization of epidermal growth factor receptor (EGFR) in ameloblastomas. Ameloblastoma samples were classified into follicular, plexiform, and basal cell types. The number of cases in each category was 17, 19 and 3, respectively. Ameloblastomas, disregarding their histological type, consist of two cell forms: peripheral columnar cells and central stellate cells. The frequency of EGFR expression was much higher in the latter than in the former (P < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
3
15
1
Order By: Relevance
“…However, Li et al [29] reported that EGFR was detected in all six of their cases of ameloblastoma. Ueno et al, [30] examined 39 cases of solid ameloblastoma and EGFR expression was found in 30 (88%). Vered et al, [19] reported that all specimens were EGFR-positive using membranous, or both membranous and cytoplasmic staining as positivity criteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, Li et al [29] reported that EGFR was detected in all six of their cases of ameloblastoma. Ueno et al, [30] examined 39 cases of solid ameloblastoma and EGFR expression was found in 30 (88%). Vered et al, [19] reported that all specimens were EGFR-positive using membranous, or both membranous and cytoplasmic staining as positivity criteria.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with the ordinary ameloblastoma [7,15,16,17,26,30,32,35], there have been only a few studies on the immunoprofile of various proteins in DA. Siar and Ng [28] described differences in the expression of some antigens such as keratin and vimentin between DA and ordinary ameloblastomas.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR expression has been demonstrated in ameloblastomas in some studies [23][24][25][26][27][28] . Among epithelial odontogenic tumors, ameloblastoma is the one which shows strong EGFR expression 29 .…”
Section: Fish Methodsmentioning
confidence: 99%